Time remaining:
solving systems of equations by substitution how do you do it

label Algebra
account_circle Unassigned
schedule 0 Hours
account_balance_wallet $5

y= 3/2 x + 3   y = -3

Jan 29th, 2015

Plug in y =-3 in the first equation.

-3 = 3/2x + 3;Add 3 to both sides.

3-3 = 3/2x + 3 + 3

0= 3/2x + 6

3/2x = -6 so x = -4 ( 2 * -6/3)

Jan 29th, 2015

Did you know? You can earn $20 for every friend you invite to Studypool!
Click here to
Refer a Friend
...
Jan 29th, 2015
...
Jan 29th, 2015
Jun 24th, 2017
check_circle
Mark as Final Answer
check_circle
Unmark as Final Answer
check_circle
Final Answer

Secure Information

Content will be erased after question is completed.

check_circle
Final Answer